1987
DOI: 10.1002/aic.690330503
|View full text |Cite
|
Sign up to set email alerts
|

A chemical reaction model for physical vapor deposition of compound semiconductor films

Abstract: A model for the physical vapor deposition of compound semiconductor films that describes film growth from component molecular beams is presented. Constitutive relationships are used in the model to account for incomplete adsorption from the incident molecular beams, emission of adsorbed components into vacuum, and surface reactions of the elemental species. The model predicts film composition and growth rate as a function of incident fluxes and substrate temperature. It is applicable for important binary and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 20 publications
4
15
0
Order By: Relevance
“…Interestingly, also for Cu‐rich films, the re‐evaporation of indium increases at a lower H 2 Se content. Obviously, a lower H 2 Se partial pressure increases re‐evaporation of indium because the equilibrium of the reactions at the film surface is pushed more to the side of the gas phases . The observation of an indium rejection phenomenon and the trends concerning the supply rates, substrate temperature, and H 2 Se content are in good agreement with investigations of Thornton et al .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Interestingly, also for Cu‐rich films, the re‐evaporation of indium increases at a lower H 2 Se content. Obviously, a lower H 2 Se partial pressure increases re‐evaporation of indium because the equilibrium of the reactions at the film surface is pushed more to the side of the gas phases . The observation of an indium rejection phenomenon and the trends concerning the supply rates, substrate temperature, and H 2 Se content are in good agreement with investigations of Thornton et al .…”
Section: Resultssupporting
confidence: 89%
“…It has to be assumed that, at the film surface, the reaction of condensed indium adatoms with Se species to In 2 Se is strongly increased if the composition of the Cu(In,Ga)Se 2 film is [Cu]/[III] ≪ 1. For Cu‐rich deposition conditions, the reaction rate for the formation of the chalcopyrite phase is faster (see also the model by Jackson et al ). The vapor pressure of the In 2 Se species is increasing with increasing temperature, causing the re‐evaporation.…”
Section: Resultsmentioning
confidence: 99%
“…The metal coevaporation follows a Cu‐poor, Cu‐rich, Cu‐poor deposition strategy, where the CIGS film will start Cu‐poor, becomes Cu‐rich during part of the deposition time, and ends Cu‐poor. The Se source was kept constant during the coevaporation to ensure a good saturation in Se and thus to prevent the loss of Ga and In . A Cu‐poor final composition is necessary to avoid segregation of Cu 2‐x Se secondary phases, which results in severe shunting of the solar cells .…”
Section: Experimental Methodsmentioning
confidence: 99%
“…It was previously reported that In and Ga loss can occur by evolution of volatile In 2 Se [18,19] and Ga 2 Se [19,20], respectively, when supply of Se or Se overpressure is insufficient during selenization. The Cu/In ratios of final CIS films shown in Fig.…”
Section: Controllability Of Composition Of Cigs Filmsmentioning
confidence: 99%